Comparative safety profile of levofloxacin versus moxifloxacin in first-line tuberculosis therapy: a pharmacovigilance study of the FAERS database - He, Yanlang; Liang, Lifen; Wei, Sheng (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to compare the safety profiles of two fluoroquinolone-containing regimens, HREL (isoniazid, rifampicin, ethambutol, levofloxacin) and HREM (isoniazid, rifampicin, ethambutol, moxifloxacin), in the treatment of drug-susceptible tuberculosis (DS-TB), focusing on adverse events (AEs) across age and gender subgroups.MethodsData were extracted from the FDA Adverse Event Reporting System (FAERS) database (2004–2024). Disproportionality analyses were conducted to assess AE signals for HREL and HREM. Pharmacovigilance metrics, including reporting odds ratios (RORs), proportional reporting ratios (PRRs), Bayesian confidence propagation neural networks (BCPNN), and empirical Bayesian geometric means (EBGMs), were calculated. Subgroup analyses were stratified by age (≥60 vs. <60 years) and gender.ResultsThe analysis included 451 HREL-related and 338 HREM-related AEs. HREL was associated with a significantly higher risk of immune reconstitution inflammatory syndrome (IRIS-TB) and drug-induced liver injury, particularly in females and patients under 60 years of age. In contrast, HREM demonstrated a higher risk of drug reaction with eosinophilia and systemic symptoms (DRESS), peripheral neuropathy, and severe hepatobiliary events such as acute liver failure. Subgroup analyses revealed that these risk profiles were influenced by age and gender. Specifically, elderly patients (≥60 years) receiving HREM had a lower risk of IRIS-TB but a higher propensity for severe liver injury. Male patients treated with HREM showed an increased risk of neurological events, including thalamic infarction.ConclusionHREM may be preferred for elderly patients (≥60 years) due to a lower risk of immune-related events like IRIS-TB, but requires careful liver monitoring. HREL could be an option for younger patients (<60 years), though vigilance for hepatotoxicity and IRIS-TB is needed, especially in females. For males on HREM, increased attention to neurological AEs is recommended.